Repeatability and agreement of Scheimpflug-based and swept-source optical biometry measurements - Sel, Saadettin; Kaiser, Delia (Contact lens and anterior eye, 2017)
Purpose: To evaluate the repeatability and comparability of biometry parameters between a Scheimpflug-based topography with axial length measurement (Pentacam AXL, Oculus, Wetzlar, Germany) and a swept-source optical biometry (IOLMaster 700, Carl Zeiss Meditec AG, Jena, Germany). Methods: A total of 50 eyes from 50 adult subjects had biometry measurements in one session three times using the Pentacam AXL and the IOLMaster 700. Keratometry, anterior chamber depth (ACD) and axial length (AL) values were obtained by both devices. Mean keratometry (Kmean) was calculated and the corneal spherocylinder was converted into power vectors (J0, J45). Repeatability was assessed based on intraclass correlation coefficient (ICC). Agreement was evaluated by linear regression analysis and Bland-Altman analysis by calculating the mean difference and 95% limits of agreement (LoA). Results: Assessment of intraoperator repeatability by means of ICC showed excellent reproducibility of measurements for both devices and all parameters examined ranging from 0.994 to 1.0. IOLMaster 700 exhibited significantly higher Kmean (p<0.001) and AL (p<0.001) values than the Pentacam AXL. Pentacam AXL showed significantly higher ACD (p<0.001) measurements than IOLMaster 700. There was no statistically significant difference of J0 (p=0.115) and J45 (p=0.255) values between Pentacam AXL and IOLMaster 700. Conclusions: Both devices provide high reproducible values for all parameters investigated. J0 and J45 values are statistically and clinically interchangeable between Pentacam AXL and IOLMaster 700. All other parameters are statistically different. In clinical practice, the differences for ACD and AL are to small and the values can be used interchangeable. However, Kmean values are clinically and statistically different and cannot be used interchangeable between the two devices.